The Relationship between Governing the Country According to the Constitution and Governing the Party According to Its Rules - Shang, Xiaoya (International Journal of Social Sciences and Public Administration, 2026)
Governance in accordance with the Constitution, as the core of the rule of law in the state, and governance of the Party in accordance with its statutes, as the core of exercising full and rigorous Party self-governance, have each attracted a wealth of research; however, academic works specifically examining the relationship between the two are relatively scarce. A systematic analysis reveals that governance in accordance with the Constitution and governance of the Party in accordance with its statutes are highly consistent in terms of content, values, objectives, internal norms and historical continuity: in terms of content, they are mutually supportive, with the Constitution affirming the Party’s leading role and the Party Constitution stipulating the requirement to abide by the Constitution and laws; in terms of values, they share a common pursuit of fairness, justice and the rule of law; in terms of objectives, they are unified by the modernisation of national governance; in terms of norms, they respectively constitute the foundations of the national and intra-Party regulatory systems; and in terms of historical continuity, both stem from the Party’s long-standing practice of leading the development of the rule of law. Clarifying the relationship between the two will help to build a legal system with Chinese characteristics and advance the realisation of the grand goal of modernising the national governance system and governance capacity.